Pharmacological and biological therapeutic strategies for osteogenesis imperfecta. Issue 4 (3rd November 2016) - Marom, Ronit; Lee, Yi‐Chien; Grafe, Ingo; Lee, Brendan
Abstract : Osteogenesis imperfecta (OI) is a connective tissue disorder characterized by bone fragility, low bone mass, and bone deformities. The majority of cases are caused by autosomal dominant pathogenic variants in the COL1A1 and COL1A2 genes that encode type I collagen, the major component of the bone matrix. The remaining cases are caused by autosomal recessively or dominantly inherited mutations in genes that are involved in the post‐translational modification of type I collagen, act as type I collagen chaperones, or are members of the signaling pathways that regulate bone homeostasis. The main goals of treatment in OI are to decrease fracture incidence, relieve bone pain, and promote mobility and growth. This requires a multi‐disciplinary approach, utilizing pharmacological interventions, physical therapy, orthopedic surgery, and monitoring nutrition with appropriate calcium and vitamin D supplementation. Bisphosphonate therapy, which has become the mainstay of treatment in OI, has proven beneficial in increasing bone mass, and to some extent reducing fracture risk. However, the response to treatment is not as robust as is seen in osteoporosis, and it seems less effective in certain types of OI, and in adult OI patients as compared to most pediatric cases. New pharmacological treatments are currently being developed, including anti‐resorptive agents, anabolic treatment, and gene‐ and cell‐therapy approaches. These therapies are under different stages of investigation from the bench‐side, to pre‐clinical and clinical trials. In this review, we will summarize the recent findings regarding the pharmacological and biological strategies for the treatment of patients with OI. © 2016 Wiley Periodicals, Inc.